Optimization of The E-Inobus Battery Pack Cooling System Design Using The Computational Fluid Dynamic Method To Overcome Condensation - Rizky Arya Saputra; Thomas Sukardi; Fredy Surahmanto (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2025)
The use of battery packs as a source of electrical energy on E-Inobus requires a cooling system, the goal is to maintain battery pack performance in optimal conditions. In its application, there are problems due to the use of a cooling system which causes an increase in air humidity inside the battery box resulting in condensation. Therefore, this study aims to obtain a design for optimizing the cooling system battery pack. This study uses the R&D method which refers to the 4D model. The subject of this research is the E-Inobus cooling system battery pack. The object of research is the development of a cooling system battery pack design to prevent condensation. Data collection was carried out to obtain data from testing the cooling system battery pack design using the Computational Fluid Dynamic (CFD) testing method to be used as input parameters in testing the cooling system battery pack optimization design. The results of the battery pack testing and the optimization of the battery pack cooling system design will later be used as control set points in the reconditioned box design. The results of this study are in the form of a reconditioned box design that has a control system. The control system is used to control air velocity and pressure, the purpose of which is to prevent condensation and to maintain fluid temperature and pressure in a balanced condition